Effect of ischemic compressions versus extracorporeal shockwave therapy on myofascial trigger points: A protocol of a randomized controlled trial - Nahomi Kuroda, Melissa [UNESP]; Thomaz de Aquino Nava, Guilherme [UNESP]; Baldini Prudencio, Caroline [UNESP]; Affonso Paulo, Daiane [UNESP]; Peixouto, Isadora [UNESP]; Yoshi Moroshima, Maiki [UNESP]; de Almeida Lourenço, Mariana; Nogueira da Silva, Caroline [UNESP]; Mércia Pascon Barbosa, Angélica [UNESP]; Rodrigues Pedroni, Cristiane [UNESP] (My University, 2023)
INTRODUCTION: The myofascial trigger points (MTrPs) are hyperirritable nodules present in a tight muscle band. Among the symptoms, pain is one of the most common, but the individuals may have other sensory, motor, and autonomic changes. Athletes can have MTrPs more intensely due to the high physical and emotional demand. There are a variety of treatments, but not all have strong or moderate evidence of their effectiveness. Thus, the aim of this study is to compare the effects of ischemic compression (IC) and extracorporeal shockwave therapy (ESWT) on pressure pain threshold immediately after the intervention and after 48h. METHODS: This randomized clinical trial was registered in the Brazilian Registry of Clinical Trial (RBR-6wryhb9) and was approved by the Research Ethics Committee (CAAE 46682921.9.0000.5406). Forty participants will be randomized to receive IC or ESWT treatment once in each MTrPs. The protocol will consist of evaluations before (T0), immediate after (T1), and after forty-eight hours (T2) of the intervention. The primary outcome will be pressure pain threshold and the secondary outcomes will be jump height, muscle strength, dorsiflexion range of motion (ROM), the correlation between MTrPs and temperature and participant's satisfaction. CONCLUSIONS: The IC and ESWT have been shown to be efficient in decreasing pain, however, the studies that compare the efficiency of these two treatments are limited in the literature, mainly in the muscles of the lower limbs, which are of great importance and are commonly injured. This study will provide evidence of the IC and ESWT in the triceps surae muscles, assisting in a better treatment for the individual with MTrPs.